Plasma glutamine responses to high-intensity exercise before and after endurance training - Kargotich, S.; Goodman, C.; Dawson, B.; Morton, A. R.; Keast, D.; Joske, D. J. L. (Research in Sports Medicine, 2005)
Glutamine responses to strenuous interval exercise were examined before and after 6 weeks of endurance training. Glutamine measures were obtained before and after the interval exercise sessions and training in untrained males assigned to training (T; n = 10) or control (C; n = 10) groups. Before training, C and T group glutamine progressively decreased (p < 0.05) by 18% and 16%, respectively, by 150-min postinterval exercise. Over the training period C group glutamine did not change, while T group values increased (p < 0.05) by 14%. After training, glutamine again decreased (p < 0.05) by similar percentages (C = 16% and T = 15%) by 150-min postinterval exercise, but the T group recorded higher (p < 0.05) resting and postexercise glutamine concentrations than the C group. Training induced increases in glutamine may prevent the decline in glutamine levels following strenuous exercise falling below a threshold where immune function might be acutely compromised.